2008
DOI: 10.1159/000113457
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Dietary Transitions in Weanling Baboons (Papio hamadryas anubis) Using Strontium/Calcium Ratios in Enamel

Abstract: Strontium and calcium are incorporated into developing teeth in a manner that reflects changing physiological concentrations in the body. A new model predicts changes in strontium/calcium (Sr/Ca) ratios in response to dietary transitions experienced at birth and during the weaning period. Microsampling of longitudinal thin sections of tooth enamel using laser ablation inductively coupled plasma mass spectrometry provides a basis for the systematic evaluation of variation in Sr/Ca ratios within the tooth crown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…They conducted spot analysis on the surfaces of tooth enamel sections. Similar BWP reconstruction using Sr concentration was performed on deciduous and permanent teeth from wild baboon individuals (Humphrey et al, 2008b). A recent study showed that changes in the Ba/Ca ratio in modern human deciduous and captive macaque permanent teeth enamel are consistent with known breastfeeding and weaning histories (Austin et al, 2013).…”
Section: Trace Element Analysis Of Tooth Enamel Apatitementioning
confidence: 95%
“…They conducted spot analysis on the surfaces of tooth enamel sections. Similar BWP reconstruction using Sr concentration was performed on deciduous and permanent teeth from wild baboon individuals (Humphrey et al, 2008b). A recent study showed that changes in the Ba/Ca ratio in modern human deciduous and captive macaque permanent teeth enamel are consistent with known breastfeeding and weaning histories (Austin et al, 2013).…”
Section: Trace Element Analysis Of Tooth Enamel Apatitementioning
confidence: 95%
“…They also examined the histological tooth sections from the 2 anubis baboons we report on here, but other than noting the earlier onset of stress as represented by accentuated lines, they were unable to come to conclusions regarding their patterning [Dirks et al, 2002]. Our novel technique for tracking weaning using strontium/calcium ratios in the teeth of these 2 animals [Humphrey et al, 2008a[Humphrey et al, , 2008b allows us to revisit the pattern of stresses and ask specifically whether stress is recorded during the weaning process.…”
Section: Foliamentioning
confidence: 99%
“…Superimposed over the background of periodic growth increments is a pattern of accentuated lines that records physiological stress during the development of the tooth [Boyde, 1990;Goodman and Rose, 1990;Guatelli-Steinberg, 2001;Dirks et al, 2002;FitzGerald and Saunders, 2005;Schwartz et al, 2006]. Here, we examine the pattern of stress in 2 anubis baboons (Papio hamadryas anubis) from Uganda, using a novel approach that combines tracing the weaning process with strontium/calcium ratios in the tooth enamel [Humphrey et al, 2008a[Humphrey et al, , 2008b and the pattern of accentuated increments to ask if weaning stress is recorded in tooth enamel. Dirks et al [2002] examined the pattern of accentuated increments in the dentitions of 2 female anubis-hamadryas hybrid baboons from Ethiopia and plotted their occurrence against rainfall records for the region over the course of their lives.…”
Section: Foliamentioning
confidence: 99%
“…14), the most widely accepted biomarker for weaning practices is the nitrogen isotope ratio measured in hair, fingernails, bone, or dentine collagen (22)(23)(24)(25). The Sr/Ca and Ba/Ca elemental ratios in tooth enamel and dentine have also proved relevant for reconstructing early-life dietary transitions (1,26,27). Nevertheless, these various methods are possibly associated with one or several drawbacks.…”
mentioning
confidence: 99%